A guerra global no cinema - Barbosa, Laura Pimentel [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
With the end of the Cold War there war many affirmations that peace would be the main characteristic of the new world order. Unfortunately, this was not what happened. Conflicts that were believed to be surpassed came back, like those of ethnic and religious motivation, besides that, new international actors became threats to international security – like those of international organized crime, international drug traffick and weapons and international terrorism. But it was with the terrorist attacks of 9/11 that the Western war effort and militarism became stronger to fight those threats. However, those efforts were performed based on the unilateral and unclear strategy named “War on Terror”. This kind of strategy, for it’s on motivation has not limits, neither in terms of space nor time. Among the weapons used in this war, besides the drones and tanks of war, we can include the products of the cultural industry. The 20th century is full of examples of the political uses of the cultural industry to promote the incentives of the masses in favor of war. The Second World War, for example, had the cultural industry and Propaganda as important means to manipulate the individual’s inner drives to promote the total war. In the 21st century, the war strategies have altered significantly, however, something remains: the relationship between war and cultural industry. Being cinema historically the flagship of this industry, one of the most profitable products of the entertainment sector and, specially in the case of the Hollywoodian cinema, who is intimately related with the American military and political sectors, it is reasonable to assume that movies are still important means of values and ideologies propagation, therefore useful to stimulate the war effort. In this dissertation, we have analyzed four movies that depicts different phases of the global war that has begun with the Gulf War and is now the “War on Terror”, the movies are: The Siege (1998), Black Hawk Down (2001), Zero Dark Thirty (2012) and American Sniper (2014). We have tried to understand how these movies depicts the enemies, what are their motivations and means of action, the western speeches that justifies the tactics used against these enemies and how these movies depicts the American military.

Com o fim da Guerra Fria, muitos foram os discursos que afirmavam que a paz seria a marca da nova ordem mundial, infelizmente esse não foi o caso. Conflitos que se acreditavam estarem superados retornaram, como os de motivação étnica e religiosa, assim como surgiram novos atores que ameaçam a segurança internacional, como o crime organizado, o tráfico internacional de drogas e armas e o terrorismo internacional. Mas foi a partir dos ataques de 11 de setembro de 2001 que o esforço de guerra e o militarismo ocidental se acentuaram para combater essas ameaças, contudo, isso foi realizado de forma unilateral e com base em uma estratégia pouco clara denominada “Guerra ao Terror”, uma guerra que por sua própria motivação, não tem limite espacial ou temporal, configurando-se, nesse sentido, como uma guerra global. Das armas utilizadas nessa guerra, além dos drones e dos tanques de guerra, também podemos incluir a mídia e a indústria cultural. O século XX é repleto de exemplos do uso político da indústria cultural para promover o direcionamento das massas e a favor de determinadas ideologias e da guerra. A Segunda Guerra Mundial, por exemplo, teve a indústria cultural e a Propaganda como meios importantíssimos para manipular as pulsões íntimas e direcionar os indivíduos em prol do esforço de guerra, promovendo a guerra total. No século XXI, a prática da guerra se alterou bastante, mas algo ainda se mantém: a relação da guerra com a indústria cultural. Sendo o cinema historicamente o carro-chefe dessa indústria, um dos produtos mais lucrativos do setor de entretenimento e, no caso do cinema hollywoodiano, intimamente envolvido com os setores militar e político, é razoável assumir que os filmes ainda são importantes meios de propagação de valores e ideologias, e portanto úteis para estimular o esforço de guerra. Neste trabalho, nós analisamos 4 filmes, um deles é puramente ficcional e os outros três são baseados em fatos reais. Em conjunto, eles nos ajudam a reconstituir a progressão histórica e discursiva da “Guerra ao Terror”, são eles: N.Y. Sitiada (1998), Falcão Negro em Perigo (2001), A Hora mais Escura (2012) e Sniper Americano (2014). Tentaremos identificar nesses filmes: como o inimigo é construído, quais são suas motivações e formas de ação; os discursos ocidentais para se combater o inimigo e justificar as táticas utilizadas contra ele; qual a imagem que esses filmes promovem dos setores militares e de suas ações.
Globar war in cinema
Keywords: Cinema; Guerra; Terrorismo; Hollywood; Indústria cultural